Caryota maxima leaf extract extends Caenorhabditis elegans lifespan by inducing mono-unsaturated fatty acid accumulation via DAF-2 signaling - Zhifan Mao; Haiyan Jiang; Lingyuan Bao; Yufeng Han; Manjiong Wang; Xiaokang Li; Conglong Xia; Jian Li; Bo Han; Bei Jiang; Zelan Hu (Acta Materia Medica, 2025)
Geroprotectors that delay aging have substantial potential for preventing and mitigating age-related diseases. Natural products derived from traditional herbal medicines are promising candidates for geroprotector discovery, because of their multi-target mechanisms and preventive health benefits. Through screening of 836 Chinese herbal medicine extracts, we identified that the leaf extract of Caryota maxima ( JM13001 ) significantly extended lifespan and healthspan in Caenorhabditis elegans . JM13001 increased total lipid content and upregulated mono-unsaturated fatty acids (MUFAs), which are known to contribute to longevity. JM13001 exerted its effects through DAF-2 signaling, thereby promoting lipid accumulation and extending lifespan in nematodes. Notably, the lifespan-extending effects of JM13001 were abolished after the loss of key enzymes responsible for converting saturated fatty acids to MUFAs or after oleic acid supplementation; therefore, its geroprotective effects are dependent on MUFAs. Chemical analysis revealed that JM13001 contains flavonoids such as rutin, isoquercitrin, and kaempferol-3-O-rutinoside, among which rutin alone was sufficient to reproduce the anti-aging and lipid accumulation promotion effects of JM13001 through DAF-2 signaling. This study identifies a novel geroprotective herbal extract and its active ingredient, thereby providing insights into the anti-aging mechanisms of natural geroprotectors via MUFA metabolism regulation.